Using redundancy to enable interactive connectivity for moving vehicles - Mahajan, Ratul (Keynote at WinMee 2009; KAIST [Daejeon, South Korea]; MPI-SWS [Saarbrucken, Germany], 2009)
Using redundancy to enable interactive connectivity for moving vehicles slideshow.